Natural products to reduce the severity of coronavirus 2019: A literature review - Sanmun, Duangmanee (Health Science, Science and Technology Reviews, 2023)
The COVID-19 pandemic may affect a large number of people. The coronavirus could re-infect someone in 2019. Nevertheless, work on developing new vaccines for lifelong immunization continues. Herbs for the intervention of life-threatening virus may be an alternative for people in order to lessen the severity of disease in susceptible patients. The objective of this paper is to present active components that have a strong potential to inhibit viral replication and reduce inflammation in patients with pneumonia. Numerous substances, including andrographolide (Andrographis), quercetin (Finger root), and curcumin (Turmeric), have biological activities. They were considered to be top-tier natural items. Thailand may be mandated to conduct research and ongoing development in the field of clinical testing on Thai and Chinese herbs, particularly artemisinin, in order to achieve this. As a result, these results will help with coronavirus infection therapy and symptom reduction in patients.